Penguatan Pemahaman Keuangan Syariah bagi Guru dan Siswa di Yayasan An-Nikmah Al-Islamiyah Phnom Penh Kamboja - Riska Shoffiyah Nissa (Journal on Education, 2023)
The rapid development of the Islamic economy has attracted the interest of the Cambodian government to develop its halal industry. For this reason, they are trying to attract investors from Muslim-majority countries to enter Cambodia. However, economic observers in Cambodia predict that Cambodia's move will be hampered by a lack of knowledge about the sharia economy. Moreover, the Muslim population in this country is only two percent of the total population. An-Nikmah Al-Islamiyah School is the best and most accomplished Islamic school in Phnom Penh, Cambodia which is located at Desa, Sangkat Chrang Chamreh 1, Khan Russey Keo, Phnom Penh, Cambodia. This school only focuses on Islamic religious teachings such as boarding schools. Many teachers and students at these schools use financial services, both bank and non-bank. However, because the country which is a Muslim minority has not yet implemented an Islamic financial system and understanding of Islamic finance is still relatively low. Their lack of understanding of Islamic finance is the reason for the need to strengthen understanding of Islamic finance through socialization and education of Islamic finance to students of An-Nikmah Al-Islamiyah school, Phnom Penh, Cambodia